(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Malnutrition among hospitalized elderly individuals is a significant concern globally, leading to increased morbidity, prolonged hospital stays, and higher healthcare costs. In Pakistan, particularly in Lahore, limited studies have assessed the prevalence of malnutrition and the quality of nutritional care in hospitals. Objective: This study aimed to determine the prevalence of malnutrition among hospitalized elderly patients, evaluate the quality of nutritional care provided, and assess patients’ perceptions of food quality in hospitals in Lahore, Punjab, Pakistan. Methods: A cross-sectional study was conducted in January and February 2018 across multiple teaching hospitals in Lahore. A total of 145 inpatients aged 55 years and above were assessed using the full version of the Mini Nutritional Assessment (MNA) tool. Quality of nutritional care was evaluated through a 39-item questionnaire administered to head nurses, and patients’ perceptions were gauged via semi-structured interviews. Anthropometric measurements, including mid-upper arm circumference (MUAC) and calf circumference, were also recorded. Results: Among the 145 patients, 77 (53.1%) were malnourished, 54 (37.2%) were at risk of malnutrition, and 14 (9.7%) had normal nutritional status. Female patients exhibited significantly lower MNA scores, particularly those aged over 65, with more than three co-morbidities, and those unable to eat independently. Medical wards had a higher prevalence of malnutrition compared to surgical wards. Quality of nutritional care was suboptimal, with inadequate staff support during meal times and a lack of personalized nutritional assessments. Conclusion: The study highlights a high prevalence of malnutrition among hospitalized elderly patients in Lahore, underscoring the need for improved nutritional screening and individualized care. Enhancing staff training, increasing dietitian presence, and fostering a patient-centered approach to nutrition could significantly improve patient outcomes.